The music room - Fiennes, William (New York : W.W. Norton & Co., 2009)
"William Fiennes spent his childhood in a moated castle, the perfect environment for a child with a brimming imagination. It is a house alive with history, beauty, and mystery, but the young boy growing up in it is equally in awe of his brother Richard. Eleven years older and a magnetic presence, Richard suffers from severe epilepsy. His mind influences the rhythms of the family and the house's internal life, and his story inspires a journey, interwoven with a loving recollection, toward an understanding of the mind." "This is a song of home, of an adored brother and of the miracle of consciousness. The chill of dark historical places coexists with the warmth and chatter of the family kitchen; the surrounding landscapes are distinguished by ancient trees, secret haunts, the moat's depths and temptations. Bursting with tender detail, The Music Room is a sensuous tribute to place, memory, and the permanence of love."--BOOK JACKET.
Also published: London : Picador, 2009.
Keywords: Fiennes, William -- Childhood and youth; Fiennes, William -- Family; Fiennes, William -- Homes and haunts -- England -- Banbury Region (Oxfordshire); Broughton Castle (England); Brothers -- England -- Biography; Epileptics -- England -- Biography; Banbury Region (Oxfordshire, England) -- Biography